Mitigation of Odor, NH3, H2S, GHG, and VOC Emissions With Current Products for Use in Deep-Pit Swine Manure Storage Structures - Chen, Baitong; Koziel, Jacek A.; Banik, Chumki; Ma, Hantian; Lee, Myeongseong; Wi, Jisoo; Meiirkhanuly, Zhanibek; O'Brien, Samuel C.; Li, Peiyang; Andersen, Daniel S.; Białowiec, Andrzej; Parker, David B. (Frontiers in Environmental Science, 2020)
Odorous gas emissions from swine production have been a concern for neighbors and communities near livestock farms. Manure storage is one of the main sources of gaseous emissions. Manure additive products are marketed as a simple solution to this environmental challenge. Manure additives are user-friendly for producers and can be applied (e.g., periodically poured into manure) without changing the current manure storage structure. Little scientific data exist on how these products perform in mitigating gaseous emissions from swine manure. The research objective was to evaluate the effectiveness of 12 marketed manure additives on mitigating odor, ammonia (NH3), hydrogen sulfide (H2S), greenhouse gases (GHG), and odorous volatile organic compounds (VOCs) from stored swine manure. A controlled pilot-scale setup was used to conduct 8-week long trials using manufacturer-prescribed dosages of additives into swine manures. Manure was outsourced from three swine farms to represent a variety of manure storage types and other factors affecting the properties. Measured gaseous emissions were compared between the treated and untreated manure. None of the tested products showed a significant reduction in gaseous emissions when all (n = 3) manures were treated as replicates. Selected products showed a wide range of statistically-significant reduction and generation of gaseous emissions when emissions were compared in pairs of manure types from one farm. The latter observation highlighted the lack of consistent mitigation of gaseous emissions by manure additives. The results of this study do not warrant full-scale trials with the tested products.